Telaah Taksonomi Keadilan Lingkungan dalam Pemenuhan Hak atas Lingkungan - Muhamad Agil Aufa Afinnas (Fakultas Hukum Universitas Islam Indonesia, 2023)
Environmental injustice and the fulfillment of the right to the environment have a relationship with each other. Environmental injustice is a real violation of the right to the environment and an inhibiting factor in fulfilling the right to the environment. Therefore, obstacles in fulfilling the right to the environment are related to environmental injustice. This study was conducted to examine the fulfillment of the right to the environment within the framework of environmental justice taxonomy which sees environmental justice as distributive justice, corrective justice, procedural justice, and social justice. This research is doctrinal legal research with a conceptual approach. The results of this study show that in the context of fulfilling the right to the environment, obstacles can be caused by distributive injustice in the form of unfair distribution of environmental benefits and risks, corrective injustice that causes weak legal protection for people’s environmental right, procedural injustice that hinders access to information, access to participation, and access to justice, and social injustice due to problems that still occur in the previous three aspects. In fact, the four aspects of environmental justice must be realized in order to fulfill the right to the environment as part of human rights.